2003
DOI: 10.1560/abr5-a6mp-5xeg-v0wf
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations and migration pathway of Juniperus thurifera L. (Cupressaceae) in the western Mediterranean region

Abstract: Random amplified polymorphic DNA (RAPD) analysis and length variations in the chloroplast trnL-trnF intergenic spacer were used to analyze the geographic structure of Juniperus thurifera L. populations in Spain and North Africa. The chloroplast DNA analysis indicated three size classes of the spacer, but was uninformative of any geographic pattern. In contrast, the RAPD data based on 127 polymorphous bands clearly showed the existence of three population groups: (a) a group comprising two populations from nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 39 publications
9
35
0
1
Order By: Relevance
“…These authors pointed out a lack of gene flow between Moroccan and Iberian populations after glacial periods (Terrab et al 2008). Our result is generally in accordance with the separate taxonomic position of the Moroccan populations (Gauquelin et al 1988;Barbero et al 1994;Adams et al 2003;Jiménez et al 2003;Romo and Boratyński 2005), treated as subspecies africana or Table 4 Analysis of hierarchical variance between Juniperus thurifera groups of populations for morphological characters (acronyms as in ultimately proposed as maroccana (till now nomen nudum) (Vela and Gauquelin 2011). The more recently published results of the studies on the genetic differentiation of conifers across the Strait of Gibraltar confirmed a high level of differences (Terrab et al 2007;Jaramillo-Correa et al 2010;Dzialuk et al 2011), however, some taxa did not follow this rule (Jaramillo-Correa et al 2010).…”
Section: Geographic Structure Of Morphological Differentiationsupporting
confidence: 86%
See 4 more Smart Citations
“…These authors pointed out a lack of gene flow between Moroccan and Iberian populations after glacial periods (Terrab et al 2008). Our result is generally in accordance with the separate taxonomic position of the Moroccan populations (Gauquelin et al 1988;Barbero et al 1994;Adams et al 2003;Jiménez et al 2003;Romo and Boratyński 2005), treated as subspecies africana or Table 4 Analysis of hierarchical variance between Juniperus thurifera groups of populations for morphological characters (acronyms as in ultimately proposed as maroccana (till now nomen nudum) (Vela and Gauquelin 2011). The more recently published results of the studies on the genetic differentiation of conifers across the Strait of Gibraltar confirmed a high level of differences (Terrab et al 2007;Jaramillo-Correa et al 2010;Dzialuk et al 2011), however, some taxa did not follow this rule (Jaramillo-Correa et al 2010).…”
Section: Geographic Structure Of Morphological Differentiationsupporting
confidence: 86%
“…Differences between subsp. thurifera and africana have also been found in the biochemical composition (Gauquelin et al 1988(Gauquelin et al , 1999Lebreton 1990;Akkad et al 2001) and genetic structure (Adams et al 2001(Adams et al , 2003Jiménez et al 2003;Terrab et al 2008). The latter study revealed strong differences between European and African populations of J. thurifera, and confirmed subsp.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations